2009
DOI: 10.1111/j.1755-148x.2009.00581.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of liposomes as drug delivery vehicles for treatment of melanoma

Abstract: Melanoma is a progressive disease that claims many lives each year due to lack of therapeutics effective for the long-term treatment of patients. Currently, the best treatment option is early detection followed by surgical removal. Better melanoma therapies that are effectively delivered to tumors with minimal toxicity for patients are urgently needed. Nanotechnologies provide one approach to encapsulate therapeutic agents leading to improvements in circulation time, enhanced tumor uptake, avoidance of the ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(66 citation statements)
references
References 117 publications
0
62
0
1
Order By: Relevance
“…Thus, in two melanoma xenograft models, phosphatidylethanolamine liposomal cisplatin was proven to have higher cytotoxicity than classic liposomes or free cisplatin, a high concentration of intratumoral drug remaining for 72 h and efficiently delivering 3.6-times more drug compared to the free drug (97)(98)(99)(100)(101)(102)(103). Niosomes are biodegradable, biocompatible, nontoxic, and nonimmunogenic having extensive solubility and flexibility.…”
Section: Liposomes and Niosomesmentioning
confidence: 99%
“…Thus, in two melanoma xenograft models, phosphatidylethanolamine liposomal cisplatin was proven to have higher cytotoxicity than classic liposomes or free cisplatin, a high concentration of intratumoral drug remaining for 72 h and efficiently delivering 3.6-times more drug compared to the free drug (97)(98)(99)(100)(101)(102)(103). Niosomes are biodegradable, biocompatible, nontoxic, and nonimmunogenic having extensive solubility and flexibility.…”
Section: Liposomes and Niosomesmentioning
confidence: 99%
“…There is substantial literature and experience during the past several decades using liposomes as nanocarriers for nucleic acids both in vitro and in vivo (50). In models of adult-type malignancies, melanoma, lung cancer, breast cancer, and ovarian cancer, targeted liposomes have been regularly used to deliver siRNA constructs (51)(52)(53). Currently, exciting applications to pediatric cancer therapeutics using liposomes as nanocarriers for siRNA involve neuroblastoma, chronic myeloid leukemia, and hepatoblastoma.…”
Section: Liposomal Therapeutic Payloads-getting the Most Bang For Thementioning
confidence: 99%
“…The in vitro results presented suggested that LCL-BUP has strong cytotoxic effects on B16.F10 melanoma cells and the anti-proliferative effects of all LCL-GC towards angiogenic endothelial cells play a role in their antitumor activity. Tran et al [134] discussed some promising new nanotechnology based therapies under development for the treatment of melanoma. This article summarized the utilization of liposomes for effective therapy of melanoma.…”
Section: Nanotechnology For Melanomamentioning
confidence: 99%